Lithium Metal Batteries: Hollow CuS Nanoboxes as Li‐Free Cathode for High‐Rate and Long‐Life Lithium Metal Batteries (Adv. Energy Mater. 7/2020). Issue 7 (18th February 2020) - Chen, Yawei; Li, Jianming; Lei, Zhanwu; Huo, Yakun; Yang, Lanlan; Zeng, Suyuan; Ding, Honghe; Qin, Yi; Jie, Yulin; Huang, Fanyang; Li, Qi; Zhu, Junfa; et al.
Abstract : CuS nanoboxes with hollow structures can accommodate volume expansion for the conversion reaction and facilitate the extraction/insertion of Li +, achieving ultra‐long cycle life (>1000 cycles) and excellent rate capability (≈371 mA h g −1 at 20 C) as Li‐free cathode for LMBs. More details can be found in article number 1903401 by Shuhong Jiao, Dongsheng Xu, and co‐workers.